Association between C-reactive protein, incident liver cancer and chronic liver disease mortality in the Linxian Nutrition Intervention Trials: a nested case-control study - Chen, Wen (Cancer Epidemiol Biomarkers Prev, 2015)
BACKGROUND: C-reactive protein is a marker of systemic inflammation that has been associated with the incidence and prognosis for a number of different cancers. Recent data suggests that C-reactive protein may be a prognostic factor for liver cancer and cirrhosis. However, few long-term studies are available. METHODS: We prospectively examined associations between serum C-reactive protein and subsequent risk of liver cancer incidence or chronic liver disease mortality in a nested case-control study performed in the Linxian Nutrition Intervention Trials cohort. Baseline serum C-reactive protein was measured for 220 incident liver cancer cases, 276 participants who died of chronic liver disease, and 1018 age-, sex-, and trial-matched controls. Unconditional logistical regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI). RESULTS: Compared to the lowest quartile, subjects in the fourth quartile of serum C-reactive protein had a higher risk of liver cancer incidence (OR=1.63, 95% CI: 1.06–2.51), with a significant p-trend across quartiles (P=0.01). The association with liver cancer was only significant among men (Q4 vs Q1, OR=2.00, 1.10–3.62), but not among women (Q4 vs Q1, OR=1.15, 0.60–2.22). For chronic liver disease deaths, the corresponding risk estimate in men and women was 2.95(1.90–4.57), with a monotonic trend (P<0.001). CONCLUSIONS: Higher serum C-reactive protein concentrations at baseline were associated with subsequent incidence of liver cancer and death from chronic liver disease. IMPACT: Our findings suggest that levels of systemic inflammation may serve as a long-term marker of liver cancer and liver disease.